The impact of the COVID-19 pandemic on the global economy: Survey-based evidence from free zones - Klaus-Jürgen Gern; Saskia Mösle (Kiel Institute for the World Economy (IfW), 2020)
In cooperation with the World Free Zones Organization, the IfW Kiel has conducted a survey among special economic zones on the impairment of their economic activities by COVID-19. The survey reveals that the vast majority of the Free Zones have already been noticeably affected and that the impact of the pandemic is expected to increase in the coming months. The authors show that COVID-19 is affecting Free Zones through various channels, in particular through its own measures to slow the epidemic, through the global decline in demand, through disruptions in value chains, and through a deterioration in financial conditions. From a regionally disaggregated view the weight of the individual channels is described. – – Das IfW Kiel hat in Zusammenarbeit mit der World Free Zones Organization eine Umfrage unter Sonderwirtschaftszonen zu den Beeinträchtigungen ihrer wirtschaftlichen Aktivitäten durch COVID-19 durchgeführt. Die Umfrage zeigt, dass die weit überwiegende Mehrzahl der Sonderwirtschaftszonen bereits spürbar betroffen ist und dass die Auswirkungen der Pandemie in den kommenden Monaten voraussichtlich noch zunehmen werden. Die Autoren stellen dar, dass COVID-19 Sonderwirtschaftszonen über verschiedene Kanäle beeinträchtigt, insbesondere durch eigene Maßnahmen zur Verlangsamung der Epidemie, durch den weltweiten Nachfragerückgang, durch Störungen in den Wertschöpfungsketten und durch eine Verschlechterung der finanziellen Rahmenbedingungen. In einer regional disaggregierten Betrachtung wird das Gewicht der einzelnen Kanäle dargestellt.
Keywords: 330; Corona crisis; world trade; Special Economic Zones; Free Zones; business survey; Coronakrise; Welthandel; Sonderwirtschaftszonen; Konjunkturumfrage